Olfactory neuroblastoma in a cat - Oliveira, Ellen Cristina de; Castro, Lucas Teixeira de; Paz, Milena Carolina; Bandinelli, Marcele Bettim; Pavarini, Saulo Petinatti (Brazilian Journal of Veterinary Pathology, 2024)
An adult, unneutered male, mixed-breed, stray domestic shorthair cat was submitted for postmortem examination at the Veterinary Pathology Service of the Federal University of Rio Grande do Sul (SPV-UFRGS). The cat presented aggression, convulsions, fainting, and drooling. In the subsequent days, the animal developed nasal and rectal bleeding. Despite treatment was performed, the cat died suddenly two days after admission.